Women’s Sexuality Across the Lifespan: A Multidisciplinary Narrative Review - Selma Dağcı; Melike Pündük Yılmaz (Women’s Health and Multidisciplinary Research, 2026)
Female sexuality is a lifelong, multidimensional phenomenon shaped by biological, psychological, cultural, and interpersonal factors. Despite its well-documented importance to health-related quality of life, it remains one of the most consistently neglected areas of women’s clinical care. This narrative review synthesizes evidence on the conceptualization, historical context, sociocultural determinants, and clinical dimensions of female sexuality, with particular attention to female sexual dysfunction (FSD), reproductive transitions, sexual trauma, cancer, and aging. The prevalence of FSD ranges from 22% to 68.9% across countries. Desire and arousal disorders predominate. Postpartum, menopausal, and oncological contexts each have distinct etiological profiles and require tailored clinical responses. Sexual trauma—affecting up to one in five women globally—is a major determinant of FSD and requires systematic clinical assessment. Sexual myths remain widespread, even among nursing and health sciences students. Despite patients’ stated preference for professional guidance, the vast majority of nurses and midwives rarely address sexual health during clinical encounters. Female sexual health should be integrated into routine clinical assessments across every stage of life. Closing the gap between acknowledged importance and actual practice requires educational reform, institutional policies, and targeted public health action.